ARGUMENT BAR MOVEMENT IN RELATIVE CLAUSES PRODUCED BY BIPA STUDENTS: AN ANALYSIS OF NOAM CHOMSKY’S GENERATIVE TRANSFORMATION - Arti Prihatini; Fauzan Fauzan; Fida Pangesti (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
This study was intended to describe (1) the characteristics of the argument bar movement in relative clauses, (2) the characteristics of the relative clause structure, and (3) the suitability of the relative clause structure produced by BIPA students. This research was a qualitative descriptive case study. This research data were relative clauses sourced from BIPA students' speeches at the beginner and intermediate levels at the University of Muhammadiyah Malang. The data collection method used was the listening method with tapping, recording, note-taking, and hidden fishing techniques. Data analysis was carried out by identifying the predication-argument relationship with theta theory, identifying the deep structure and surface structure, analyzing movement objectives, movement traces, and movement consequences by utilizing the subjacency condition theory. The results showed that the characteristics of the argument bar movement in the relative clauses generated by 92% of BIPA students were in the form of short movements and did not exceed one bounding node. Based on the Indonesian language rules, most of the relative clauses produced by BIPA students were appropriate (75%). It shows that BIPA students have fully understood the relative clause structure.